Laparoscopic Resection of Appendiceal Schwannoma - Toru Imagami; Satoru Takayama; Yohei Maeda; Ryohei Matsui; Masaki Sakamoto; Hisanori Kani (Case Reports in Surgery)
Background. Schwannoma arises from Schwann’s cell of the neural sheath. Schwannoma of the large intestine, particularly of the appendix, is rare. We report a case of appendiceal schwannoma resected using laparoscopic surgery. Case Presentation. A 75-year-old man was referred to our hospital for abdominal fullness and nausea since 2 months. Abdominal CT revealed a well-demarcated oval mass of 25 mm at the tip of the appendix. Contrast-enhanced CT revealed a lesion with gradually enhanced contrast from the arterial phase to the equilibrium phase. Abdominal US revealed a well-demarcated hypoechoic tumor. Preoperative diagnosis indicated appendiceal mesenchymal or neuroendocrine tumor. Ileocecal resection with D3 lymph node dissection was performed. Pathological and immunohistochemical findings confirmed the diagnosis of appendiceal schwannoma. Conclusions. For determining the surgical procedure of nonepithelial tumor of the appendix, preoperative diagnosis of mesenchymal or neuroendocrine tumors is required. However, appendiceal schwannoma is extremely rare, and its characteristic findings have not yet been established. Accumulating cases of appendiceal schwannomas is necessary for improving imaging diagnosis and surgical treatment.